Development of a spherical motor with a 3-DOF sensing system - Guo, Jinjun (2016)
The thesis proposes a new design of a spherical wheel motor (SWM) with three layers of permanent magnets (PMs) located both inside and outside of double layers of electrical magnets (EMs), so as to fully utilize the magnetic field generated by the EMs and enhance the inclination torque density. The inclination torque is generally weak due to the limited number and space for the PMs and EMs involved in inclination compared to spinning. Finite element modeling (FEM) has been utilized for simulation, and important design parameters are optimized to maximize the inclination torque. The FEM modeling has been verified by experiments with discrepancy of less than 10% achieved. The optimized design can generate strong inclination torque which can support heavy loadings. Iron stator cores are applied in the new design to improve magnetic torque, and the magnetic field distribution (MFD) and magnetic torque become nonlinear due to magnetic saturation characteristics of the iron cores. Based on the analysis of the MFD of the whole SWM applying different current inputs, the thesis has constructed a dynamic model for SWMs with current inputs within the working range. A multi-DOF non-contact sensing system based on magnetic sensors and neural networks (NNs) is proposed. NNs are applied to approximate the function between orientations and MFD. The proposed sensing system is simulated and verified by experimental investigations. The sensing error to working range ratio is about 1.4%, which verifies its feasibility. With the proposed SWM design with enhanced torque capability, dynamic model and sensing system, the present findings provide strong basis to realize an integrated system of an SWM and take it a step closer to industrial applications.